How to teach entrepreneurship using serious games and web 2.0 - Protopsaltis, Aristidis; Hetzner, Sonia; Borotis, Spiros; Connolly, Thomas; Hainey, Thomas (14th IEEE International Conference on Advanced Learning Technologies, ICALT 2014, 2014)
This paper reports on the main piloting of the StartUp_EU project (http://startup-eu.net/). StartUp_EU targets secondary schools and simulates the process of starting up a high tech company. The project developed a series of mini-games, a Web2.0 platform and a collaborative competition for students, between 14 and 18 years of age. 243 students participated in the competition, completing a series of 8 tasks, starting from a business idea to a product and creating an elevator pitch. Pre-competition and post-competition questionnaires were collected and the results on participants' perception of the learning experience regarding entrepreneurship using serious games and Web 2.0 technologies, presented here.
Keywords: game-based learning; entrepreneurship; serious games; secondary education; Web2.0